Os efeitos da intervenção fonoaudiológica sensório-motora oral sobre a sucção não-nutritiva em recém-nascidos pré-termo - Carnetti, Mara Gislaine (2005)
The speech-language pathology intervention in newborn infants with oral motor system problems during their admission in the neonatal intensive care unit (NICU) can helps not only the oral motor development, but also their global development, minimizing future language problems. The aim of this study was to determine if the oral motor sensorial system intervention influences or modifies non-nutritive sucking (SNN) of preterm infants (RNPT) admitted in the NICU of the University Hospital of Santa Maria. A total of 20 RNPT were enrolled in this study subdivided into an experimental group (GE) and a control group (GC), with 10 infants in each group. Inclusion criteria were preterm babies clinically stable at the moment of their transition from tube to bottle feeds, without alterations in their defense reflections (cough, bite fasic and gag) and after written informed consent was obtained from parents and/or legal representation. Exclusion criteria included preterm infants with congenital malformation of head and neck, genetic syndrome, intracranial hemorrhage, perinatal asphyxia and bilirubin encephalopathy and/or kernicterus. Both groups were submitted to fonoaudiological evaluation and re-evaluation based in Hernandez (2001) and were observed: the behavior state (EC), oral reflections, reactions of the stimulus and same aspects of non-nutritive suking like force, number of sucking in the first three burst and the time of pauses among the sucking bursts. The GE received twice a day oral motor sensorial system stimulation, embodied the stimulation extra motor-sensorial and intra-oral, being that, after the conclusion of the same one, the specific proceeding were indicted in the protocol that went along with each RN, this protocol was based in Medeiros et al. (2003). When comparing groups GE and GC, we noticed that the oral motor sensorial system intervention was good in order to provide a better organization in the sucking standard of the RNs that were stimulated. When comparing the obtained results in the valuation and re-valuation of the stimulated group relating to the SNN, we found out that there was not difference statistically significant, meantime, it was observed that, when talking about the number of sucking, there was a decrease in the valuation bursts and in the re-valuation, as well, and in this last one, the numbers were closer, and it indicate that the stimulation work might help in the organization of the RN in order to keep a sucking standard with closer indexes. According to the time of pauses, it was noticed that the value of the p was higher than 0,05, however it was noticed the considerable difference in the second time of the pause, that suggests that with the oral motor sensorial system stimulation program the RN organized the time of the pauses among the sucking, providing a better synchronization among the bursts of sucking, though there was a decrease in the valuation and re-valuation, this way it was observed a higher approach in the valuation, different to the obtained results in the group that received stimulation. When talking about the time of the pauses, it was noticed that the value of p was higher that 0,05, however it was also observed a considerable difference of the valuation and re-valuation, and the higher values in this last one, it suggests that the RN had more fatigue comparing to the GE. About the time of confining, comparing the groups, there was not difference statistically significant, it showed that the oral motor-sensorial stimulation program did not accelerated the process of hospital discharge.